2007
DOI: 10.1136/bjsm.2006.032417
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of eccentric training as treatment for patellar tendinopathy (jumper’s knee): a critical review of exercise programmes

Abstract: Most studies suggest that eccentric training may have a positive effect, but our ability to recommend a specific protocol is limited. The studies available indicate that the treatment programme should include a decline board and should be performed with some level of discomfort, and that athletes should be removed from sports activity. However, these aspects need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
102
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 25 publications
1
102
0
9
Order By: Relevance
“…34 There were no studies identified that directly relate to EE in gluteal tendinopathy. However, studies demonstrate good results with EE in other tendinopathies including patellar tendinopathy 71 and achilles tendinopathy. 72 EE could therefore be considered a potential component of GTPS rehabilitation.…”
Section: Physiotherapy -Eccentric Exercise (Ee)mentioning
confidence: 97%
See 1 more Smart Citation
“…34 There were no studies identified that directly relate to EE in gluteal tendinopathy. However, studies demonstrate good results with EE in other tendinopathies including patellar tendinopathy 71 and achilles tendinopathy. 72 EE could therefore be considered a potential component of GTPS rehabilitation.…”
Section: Physiotherapy -Eccentric Exercise (Ee)mentioning
confidence: 97%
“…These exercises have been shown to have good effect in Achilles tendinopathy 72 and patellar tendinopathy. 71 There are no studies specific to EEs for GTPS. EEs may be considered as the most appropriate exercise method for GTPS; studies would be needed to evaluate this.…”
Section: Implications For Practicementioning
confidence: 99%
“…J Orthop Sports Phys Ther 2011;41(8):581-591, Epub 12 July 2011. doi:10.2519/jospt.2011 Since its publication in 1998, the instrument has been increasingly used to assess changes in the severity of symptoms in athletes with patellar tendinopathy after therapeutic intervention. 7,9,15,18,21,38,40 Important advances in the understanding of tendon pathology and clinical trials conducted by several research groups have made the VISA-P a widely accepted and valuable tool of reference for the assessment of patellar tendinopathy. …”
mentioning
confidence: 99%
“…[2] Evidence generally supports the use of CS injections, [1,3] because injected CSs decrease swelling and pain, permitting improved range of motion and thereby facilitating rehabilitation. [4][5][6][7] We chose CS injections frequently for all regions except MTP. Triamcinolone is the preferred CS in the literature, and comparisons between types of CS indicate that triamcinolone hexacetonide is superior to betamethasone.…”
Section: Discussionmentioning
confidence: 99%